Theoretical Calculations of Economic Life of Firefighting Appliances Based on Chassis Tatra in the South Moravian Region - Ladislav Janosik; Ivana Janosikova; Pavel Polednak (Communications - Scientific letters of the University of Zilina, 2018)
This paper is focused on the evaluation of economic data obtained from operational records of firefighting equipment with a focus on firefighting and rescue appliances, especially on exit vehicles based on the chassis CAS 20 – TATRA T815-231R55 18 325 4x4.2. These vehicles have been operated by professional units of the Fire and Rescue Service in the South Moravian Region since September 2013. The producer of firefighting superstructures WISS GROUP, Bielsko-Biala, Poland, was a supplier of all these vehicles. The paper’s aim is to specify the optimum lifetime of the firefighting vehicles by the analysis of firefighting vehicles’ economical operation. Theoretical calculations of the optimum lifetime have been processed with implementing both the method of exponential trends and the Brown method. The residual value of vehicles has been calculated both according to the current Czech tax law, and to the Expert Standard Valuation of motor vehicles in force in the Czech Republic.